2019
DOI: 10.1080/16549716.2019.1672314
|View full text |Cite
|
Sign up to set email alerts
|

Causes and contributing factors of maternal mortality in Bosaso District of Somalia. A retrospective study of 30 cases using a Verbal Autopsy approach

Abstract: Background: Somali women suffer from one of the highest maternal mortality rates in the world. Somalia characterises a specific low-income country situation with a mix of newly urbanized and nomadic culture combined with a frail health care infrastructure set in a postconflict era. Very little is known about the effects that these contextual factors can have on maternal mortality. Objectives: To explore and describe causes and contributing factors concerning maternal deaths in the Bosaso District, Puntland Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 18 publications
(23 reference statements)
5
33
0
5
Order By: Relevance
“…We raise this point because factors like anemia and malaria, which have higher frequency rates in the category of indirect causes, attract more attention and equal concern since these are treatable illnesses which should not cause fatalities to the extent of their current state. The findings discussed here support the literature review above that in many African countries, people become victims either of treatable diseases or due to lack of appropriate care and drugs (Pheage 2017;Aden et al 2019). Concerning the direct causes, a timely arrival at a medical facility, enhanced obstetric as well as midwifery training for medical personnel and for traditional birth attends (TBAs) could extensively reverse the situation.…”
Section: Analysis and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We raise this point because factors like anemia and malaria, which have higher frequency rates in the category of indirect causes, attract more attention and equal concern since these are treatable illnesses which should not cause fatalities to the extent of their current state. The findings discussed here support the literature review above that in many African countries, people become victims either of treatable diseases or due to lack of appropriate care and drugs (Pheage 2017;Aden et al 2019). Concerning the direct causes, a timely arrival at a medical facility, enhanced obstetric as well as midwifery training for medical personnel and for traditional birth attends (TBAs) could extensively reverse the situation.…”
Section: Analysis and Discussionsupporting
confidence: 87%
“…Together, these factors are described to be among the most common causes of maternal mortality. However, there is need to note that sometimes death of an expecting mother may occur due to mismanagement by the medical personnel or the patients themselves, as Aden et al (2019) found out in their study undertaken in Bosasso District in the State of Puntland, Somalia.…”
Section: Maternal Mortality In a Global Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The causes of maternal morbidity and mortality are multifactorial. An in-deeply analysis on the trends of maternal health in Somalia related to demographic, social behavioral, nutritional, and health services related factors are associated with poor maternal health outcomes [13].…”
Section: Introductionmentioning
confidence: 99%